2015
DOI: 10.1097/jcp.0000000000000397
|View full text |Cite
|
Sign up to set email alerts
|

Linking Annual Prescription Volume of Antidepressants to Corresponding Web Search Query Data

Abstract: Persons using the Internet to retrieve medical information generate large amounts of health-related data, which are increasingly used in modern health sciences. We analyzed the relation between annual prescription volumes (APVs) of several antidepressants with marketing approval in Germany and corresponding web search query data generated in Google to test whether web search query volume may be a proxy for medical prescription practice. We obtained APVs of several antidepressants related to corresponding presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The final output, the Google Trends score, is not meant to mirror, at least directly, the epidemiology of a given drug, but reflects the interest of the general public in that same pharmacological agent, with the final score potentially influenced also by media clamor at the time. Nevertheless, and quite understandably, the larger the use of a new therapy, the bigger the general interest of patients and physicians for that drug, as reliably proven by some earlier investigations (16,17,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final output, the Google Trends score, is not meant to mirror, at least directly, the epidemiology of a given drug, but reflects the interest of the general public in that same pharmacological agent, with the final score potentially influenced also by media clamor at the time. Nevertheless, and quite understandably, the larger the use of a new therapy, the bigger the general interest of patients and physicians for that drug, as reliably proven by some earlier investigations (16,17,19).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, a value of 100 reflects the peak popularity for the term, a value of 50 means that the term had half the peak popularity, whereas a value of 0 means the term was less than 1% as popular as the peak. The use of Google Trends is becoming increasingly frequent in biomedical research, and this tool has already been profitably used in many scientific publications, especially for investigating epidemiological trends of specific pathological conditions (15), and also as a reliable means for reflecting real use of some types of drugs such as antibiotics (16) and antidepressants (17). Due to increasing use of DOACs in routine practice, we hence planned this original study to investigate the worldwide popularity of these agents in terms of Google Web searches of DOACs.…”
Section: Introductionmentioning
confidence: 99%
“…Internet, social media, and online technologies have become powerful tools in the mental health sector, leading transformations that go from infodemiology and infoveillance—the monitoring of suicidal tendancies [3-6] or medical antidepressants prescription behaviors [7], for example, with a Google Trends-based approach—to crowdsourcing for conducting randomized trials for the purpose of scientific research [8], not to mention the delivery of evidence-based therapies targeting various mental illnesses [9,10]. Some thought papers have studied the evolution of telepsychiatry, also called “e-mental health care,” where this expression defines a “practice supported by electronic processes and communication, (including) mental health applications and links on mobile phones” and services of “information (delivering), peer support services, computer- and Internet-based programs, virtual applications, and games, as well as real time interaction with trained clinicians” [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more topics on relating Google data with official health data have been visited, as in the case of suicide rates, where it has been show that Google queries can be used to monitor the risk of suicide [18,19]. On a different direction, there has been shown that correlations exist between Google Trends data and prescription drugs issuing [20,21] and revenues [22]. Apart from prescription drugs, focus has been given to illegal drugs as well, with notable examples including the tracking of dabbing in the US [23], Krokodil in Russia [24], and Methamphetamines in Central Europe [25].…”
mentioning
confidence: 99%